GPR56 homozygous nonsense mutation p.R271* associated with phenotypic variability in bilateral frontoparietal polymicrogyria - (:unkn) unknown (My University, 2018)
Polymicrogyria is a disorder of neuronal migration characterized byexcessive cortical folding and partially fused gyri separated by shallow sulci.Homozygous mutations in the GPR56 gene, which regulates migration ofneural precursor cells, are associated with bilateral frontoparietal polymicrogyria(BFPP) syndrome including white matter changes, brainstem and cerebellarinvolvement. Herein, we describe three siblings of consanguineous parentswith a homozygous germline mutation (p.R271*) located in the seventh exonof the GPR56 gene that was previously detected in only one Portuguesepatient. Phenotypic/genotypic relationships were analysed according to theclinical characteristics in only index patient. While earlier reported patient wasexhibiting seizures provoked by hot water, macrocephaly, cerebellar/brainstemhypoplasia and corpus callosum abnormalities, the index patient showed onlyhypoplasia of brainstem, focal onset bilateral tonic clonic seizure. Despite thephenotypic similarities in two patients, the potential causes of the variationin the expression of the p.R271* variant between the two affected familiesmight be genetic or epigenetic factors beyond the GPR56 gene. Consequently,the present findings show that the same mutation in GPR56 gene can havedifferent phenotypic effects. Therefore, additional functional studies areneeded to detect the phenotypic spectrum of the p.R271* mutation in GPR56,and provide insight into the mechanism of normal cortical development andregional patterning of the cerebral cortex.
Keywords: Pediatri